STATISTICAL ANALYSIS OF COMINFORM PRISONERS FROM THE TERRITORY OF THE AUTONOMOUS REGION OF KOSOVO-METOHIJA (Heritage, 2024)
The conflict with the Communist Information Bureau and the severing of allied relations with the Soviet Union marked a turning point in the development of the Communist Party of Yugoslavia. From being a loyal follower of the USSR, communist Yugoslavia became the first country to develop its own path to socialism, and Josip Broz was the first communist leader to say a historic no to Josef Vissarionovich Stalin. The consequences of this decision for the country were manifold, on a political, economic, military and social level. One of them was that repression was launched against anyone who expressed sympathy for the USSR or criticized the new Yugoslav policy. The result was the arrest and interrogation of thousands of people “for their real or alleged support for the Cominform” and their punishment and incarceration in prisons and camps throughout Yugoslavia. One of the most famous and notorious was the camp complex on the Adriatic Island of Goli Otok, which was set up for the very purpose of punishing “cominformers” from all over the country. In this paper, we have attempted to statistically analyze the structure of the Goli Otok prisoners from the Autonomous Region of Kosovo-Metohija (AKMO) based on the relevant literature and historical sources.
Keywords: Goli otok, Cominform, Kosovo and Metohija, prisoners, repression, communists